LINGUISTIC LANDSCAPE IN TOURISM SPACES IN PUNCAK - Misran; Masrun Masrun; Aprijon Efendi (Sunan Kalijaga State Islamic University Yogyakarta, 2025)
This study investigates the linguistic landscape in tourism spaces in Puncak, a popular tourist destination in West Java, Indonesia. It explores the diversity, distribution, and functions of languages used, as well as the reasons why this phenomenon occurred in this specific area, where people host tourists. Using a qualitative approach, this research examines language use in signs, advertisements, and public notices, revealing the socio-cultural and economic dynamics that shape language choices. Findings highlight the prominence of three languages: Indonesian, Arabic, and English, reflecting local identity, the influence of Middle Eastern tourists, and global tourism trends. The study also investigates how multilingualism, cultural identity, and the commodification of languages interact in tourism. By examining the symbolic and informational roles of language in public spaces, this research contributes to an understanding of sociolinguistic diversity in multicultural tourism settings. It offers insights for the development of inclusive language policies, especially in tourism spaces.